Peripheral osteoma of the body of mandible in a 23-year-old female - Saini, Saurabh; Khan, Saquib Riyaz; Agrwal, Shradha; Singhal, Vanshika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Mandibular osteomas are rare, benign, slow-growing bone tumors most commonly found in the craniofacial region. Although typically asymptomatic, they can cause localized swelling, pain, or functional disturbances, such as difficulty chewing, when they grow large enough to impact surrounding structures. Peripheral osteomas, which arise on the external surface of the mandible, represent a distinct variant of these tumors. The lesion typically grows slowly and, on radiographs, presents as a well-defined radiopaque mass. Mandibular osteomas are often discovered incidentally due to their slow growth and lack of symptoms. However, as demonstrated in this case, they can lead to significant functional impairment, such as chewing difficulties, when they grow large enough. Surgical excision remains the treatment of choice, offering excellent outcomes with minimal risk of recurrence. Early diagnosis and appropriate surgical intervention are crucial in managing peripheral osteomas of the mandible. With proper treatment, patients can expect favourable outcomes and minimal complications.